PENGARUH VARIASI FAKTOR AIR SEMEN TERHADAP KUAT TEKAN DAN MORFOLOGI BETON GEOPOLIMER FLY ASH TIPE F - Eliza Siti Syarifah; Wahyu Kartini; Sumaidi (Racic : Rab Construction Research, 2026)
Geopolymer concrete is one of the alternative substitutes for conventional concrete by utilizing fly ash as a cement substitute. This study examines the effect of varying water-to-cement ratios of 0.3, 0.4, and 0.5 on the morphology and compressive strength of type F fly ash-based geopolymer concrete. The activators used were 10 M NaOH and Na₂SiO₃ with a ratio of 1:1 through the dry mixing method. Morphological testing was conducted using SEM-EDX, and compressive strength was tested using a UTM at 28 days. The results showed that conventional concrete with W/C 0.3 had a dense morphology with low porosity, producing a compressive strength of 32.38 MPa. W/C 0.4 showed a rounded morphology with moderate porosity and a compressive strength of 31.82 MPa. Meanwhile, W/C 0.5 exhibited a rough morphology with high porosity and a compressive strength of 19.48 MPa. In contrast, all variations of geopolymer concrete showed loose morphology, high porosity, and low compressive strength 2.36 MPa W/C 0.3, 1.32 MPa W/C 0.4, and 1.32 MPa W/C 0.5. On average, the compressive strength of geopolymer concrete decreased by 93.93% compared to conventional concrete. The poor performance was due to the incomplete formation of N–A–S–H gel, as water could not dissolve Na₂SiO₃ in the dry mixing method, preventing optimal bonding between fly ash particles. Therefore, type F fly ash geopolymer concrete using the dry mixing method cannot be considered a substitute for Portland cement conventional concrete.